Access to Care, Provider Choice, and the Infant Health Gradient - Aizer, Anna; Lleras-Muney, Adriana; Stabile, Mark (American Economic Review, 2005)
Access to Care, Provider Choice, and the Infant Health Gradient by Anna Aizer, Adriana Lleras-Muney and Mark Stabile. Published in volume 95, issue 2, pages 248-252 of American Economic Review, May 2005